2016
DOI: 10.1155/2016/2640746
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Inhibition of Gal‐3 in Mesenchymal Stem Cells Enhances Their Capacity to Promote Alternative Activation of Macrophages in Dextran Sulphate Sodium‐Induced Colitis

Abstract: Transplantation of mesenchymal stem cells (MSCs) reduces the severity of dextran sulphate sodium- (DSS-) induced colitis. MSCs are able to secrete Galectin-3 (Gal-3), a protein known to affect proliferation, adhesion, and migration of immune cells. We investigate whether newly synthetized inhibitor of Gal-3 (Davanat) will affect production of Gal-3 in MSCs and enhance their potential to attenuate DSS-induced colitis. Pharmacological inhibition of Gal-3 in MSCs enhances their capacity to promote alternative act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…Recently, by using murine model of acute colitis induced by dextran sodium sulfate (DSS), we showed that pharmacological inhibition of Gal‐3 in BM‐MSCs enhances their capacity to promote alternative activation of peritoneal macrophages in vitro and in vivo . Injection of BM‐MSCs cultured in the presence of Gal‐3 inhibitor increased concentration of IL‐10 in sera of DSS‐treated animals and markedly enhanced presence of alternatively activated and IL‐10 producing macrophages in the colons of DSS‐treated mice leading to the attenuation of colitis . In accordance with these findings, results obtained in a large number of clinical trials indicate therapeutic potential of MSCs in the treatment of inflammatory bowel diseases (IBDs).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Recently, by using murine model of acute colitis induced by dextran sodium sulfate (DSS), we showed that pharmacological inhibition of Gal‐3 in BM‐MSCs enhances their capacity to promote alternative activation of peritoneal macrophages in vitro and in vivo . Injection of BM‐MSCs cultured in the presence of Gal‐3 inhibitor increased concentration of IL‐10 in sera of DSS‐treated animals and markedly enhanced presence of alternatively activated and IL‐10 producing macrophages in the colons of DSS‐treated mice leading to the attenuation of colitis . In accordance with these findings, results obtained in a large number of clinical trials indicate therapeutic potential of MSCs in the treatment of inflammatory bowel diseases (IBDs).…”
Section: Introductionsupporting
confidence: 58%
“…MSCs produce Galectin‐3 (Gal‐3), a protein known to affect proliferation, adhesion, and migration of immune cells . Recently, by using murine model of acute colitis induced by dextran sodium sulfate (DSS), we showed that pharmacological inhibition of Gal‐3 in BM‐MSCs enhances their capacity to promote alternative activation of peritoneal macrophages in vitro and in vivo . Injection of BM‐MSCs cultured in the presence of Gal‐3 inhibitor increased concentration of IL‐10 in sera of DSS‐treated animals and markedly enhanced presence of alternatively activated and IL‐10 producing macrophages in the colons of DSS‐treated mice leading to the attenuation of colitis .…”
Section: Introductionmentioning
confidence: 99%
“…Simovic et al found that Gal‐3 can promote the activation of the NOD‐like receptor family, the pyrin domain containing 3 (NLRP3) inflammasome, and the production of IL‐1β in macrophages . Inhibition of Gal‐3 activation pushes macrophages toward M2 polarization via upregulating the expression of IL‐10 in vitro and in vivo, suggesting that AGEs/Gal‐3 play roles in macrophage polarization that modulate the responsiveness of innate and adaptive immunity.…”
Section: Micro‐environmental and Intracellular Metabolism On Atm Polamentioning
confidence: 99%
“…In the peritoneal cavity of mice with acute colitis, the amount of CD206+ M2 macrophages was significantly increased by MSCs with IL-1 pretreatment, which inhibited the number of CD11c+ M1 macrophages, thus alleviating inflammatory responses in the intestinal mucosa [ 84 ]. Semitic et al also demonstrated that MSCs mediated the alternative activation of macrophages through the inhibition of galectin-3 [ 85 ]. We have demonstrated that hucMSCs could repair DSS-induced IBD through the regulation of 15-LOX-1 expression and the modulation of inflammatory responses in macrophages [ 86 ].…”
Section: Mesenchymal Stem Cells Regulate Macrophages To Treat Inflammmentioning
confidence: 99%